PANORAMA HISTORY OF SOCIAL EXCHANGE THEORY: SEJARAH PANORAMA TEORI PERTUKARAN SOSIAL - Sufyanto, Sufyanto (Kanal: Jurnal Ilmu Komunikasi, 2024)
This study discusses the history and development of social exchange theory, focusing on basic concepts such as giving, receiving, and returning. This theory is influenced by various figures, including Marcel Mauss, George Homans, and Peter Blau. Mauss in "The Gift, Forms and Functions Exchange in Archaic Societies" articulates giving as a form of exchange involving obligations to receive, give, and return. Homans in "Social Behavior: Its Elementary Forms" explains social behavior as an exchange of activities and gifts, while Blau in "Exchange and Power in Social Life" analyzes more complex social structures and regulates social power through the exchange process. This study uses a literature review approach to understand the history and development of social exchange theory, as well as to analyze the relationship between social behavior and the social environment. The results of the study show that social exchange theory provides broad insights into how society creates and maintains social organizations through exchange. Thus, this study makes a significant contribution to understanding social exchange theory and its applications in various social contexts.